2020
DOI: 10.26633/rpsp.2020.103
|View full text |Cite
|
Sign up to set email alerts
|

Educational strategies for human resources in home health care: 8 years’ experience from Brazil

Abstract: Objective. To analyze characteristics, enrollments and completion rates of healthcare professionals enrolled in Self-Instructional Online Courses of the Home Health Care Multicentre Qualification Program, developed by the Ministry of Health and the Universidade Aberta do SUS (UNASUS), and its relationship with Home Health Care Teams implementation. Methods. Data were extracted from the Self-Instructional Online Courses’ UNASUS enrollment platform database (2012-2018), cross-referenced with the Health Facilitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…[9][10][11] A study has shown that continuing education courses on oropharyngeal cancer led to improvement in some outcomes related to the subject matter, such as knowledge, performance, and confidence. 12 In Brazil, TelessaúdeRS/UFRGS and the Open University of Brazilian National Health System (UNA-SUS), both initiatives of the Ministry of Health, have promoted DL courses, [13][14][15][16] with positive evaluation by their participants. 13 These approaches appear to be useful to target the different professions involved in primary care, addressing specific needs for continuing education.…”
Section: Declaration Of Interestsmentioning
confidence: 99%
“…[9][10][11] A study has shown that continuing education courses on oropharyngeal cancer led to improvement in some outcomes related to the subject matter, such as knowledge, performance, and confidence. 12 In Brazil, TelessaúdeRS/UFRGS and the Open University of Brazilian National Health System (UNA-SUS), both initiatives of the Ministry of Health, have promoted DL courses, [13][14][15][16] with positive evaluation by their participants. 13 These approaches appear to be useful to target the different professions involved in primary care, addressing specific needs for continuing education.…”
Section: Declaration Of Interestsmentioning
confidence: 99%